2015
DOI: 10.1038/srep08753
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of thermogenic Arum concinnatum reveals the molecular components of floral scent production

Abstract: Several plant species can generate enough heat to increase their internal floral temperature above ambient temperature. Among thermogenic plants, Arum concinnatum shows the highest respiration activity during thermogenesis. However, an overall understanding of the genes related to plant thermogenesis has not yet been achieved. In this study, we performed de novo transcriptome analysis of flower organs in A. concinnatum. The de novo transcriptome assembly represented, in total, 158,490 non-redundant transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 78 publications
0
21
0
1
Order By: Relevance
“…A number of reports have been published regarding the interspecific relationships between Opisthopappus species based on molecular markers (Wang, 2013;Wang and Yan, 2013); however, such research has been limited due to the lack of specific genomic information on Opisthopappus. Compared with other EST-SSR markers of plants (Kudapa et al, 2012;Onda et al, 2015;Wei et al, 2016;Li et al, 2018), the developed Opisthopappus transcriptomic SSR markers showed a high level of genetic diversity (Table 2), which indicated that the identified microsatellite loci possessed high allele numbers and heterozygosity, which provided efficient genetic markers for Opisthopappus populations.…”
Section: Genetic Differentiation and Phylogenetic Relationships Betwementioning
confidence: 97%
“…A number of reports have been published regarding the interspecific relationships between Opisthopappus species based on molecular markers (Wang, 2013;Wang and Yan, 2013); however, such research has been limited due to the lack of specific genomic information on Opisthopappus. Compared with other EST-SSR markers of plants (Kudapa et al, 2012;Onda et al, 2015;Wei et al, 2016;Li et al, 2018), the developed Opisthopappus transcriptomic SSR markers showed a high level of genetic diversity (Table 2), which indicated that the identified microsatellite loci possessed high allele numbers and heterozygosity, which provided efficient genetic markers for Opisthopappus populations.…”
Section: Genetic Differentiation and Phylogenetic Relationships Betwementioning
confidence: 97%
“…This strategy can enrich the large amounts of expressed sequence data for non-model organisms for which the reference genome or transcriptome is not available (Martin & Wang, 2011). Several non-model organisms in the Araceae family, including Z. aethiopica (Cândido et al, 2014) Arum concinnatum (Onda et al, 2015), Anthurium andraeanum (Tian et al, 2013; Yang et al, 2015; Li et al, 2015), Pinellia ternate (Wang et al, 2014), Amorphophallus konjac and A. bulbifer (Zheng et al, 2013; Diao et al, 2014), have been recently studied by transcriptome sequencing, which has provided a better understanding of these crops. EST-SSR markers have been successfully characterized and developed in P. ternate (Wang et al, 2014), A. konjac and A. bulbifer (Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…本研究组在对玉兰生热 期间蛋白表达的研究中发现, UCP与AOX均有一定水 平的表达(未发表数据). Onda等人 [68] 发现, 生热植物 [69,70] . 并且, 这些差 异表达基因的蛋白产物大多定位于线粒体和叶绿体, 与线粒体功能紧密相关 [62] .…”
Section: 此外 Ucp1过表达亦会导致碳同化以及气孔导度的增unclassified